Frontispiece: Recent Progress in the Synthesis of the Monocarba‐closo‐dodecaborate(−) Anions. Issue 39 (11th July 2019) - Kanazawa, Junichiro; Kitazawa, Yu; Uchiyama, Masanobu
Abstract : Carboranes : There has been a rapid growth in studies on the monocarba‐ closo ‐dodecaborate(−) anion, one of the most stable anions known. Development of novel functional molecules utilizing its unique properties have been hampered by the state of synthetic chemistry of the anion. Recent progress, however, moves this species beyond its well‐established role of highly stable counter‐ion. For more information, see the Concept article by J. Kanazawa, Y. Kitazawa and M. Uchiyama on page 9123 ff.